Resveratrol Inhibits Oesophageal Adenocarcinoma Cell Proliferation via AMP-activated Protein Kinase Signaling - Fan, Guang-Hua; Wang, Zhong-Ming; Yang, Xi; Xu, Li-Ping; Qin, Qin; Zhang, Chi; Ma, Jian-Xin; Cheng, Hong-Yan; Sun, Xin-Chen (Asian Pacific journal of cancer prevention : APJCP, 2014)
Resveratrol has been examined in several model systems for potential effects against cancer. Adenosine monophosphate-activated protein kinase (AMPK) is reported to suppress proliferation in most eukaryocyte cells. Whether resveratrol via AMPK inhibits proliferation of oesophageal adenocarcinoma cells (OAC) is unknown. The aim of this study was to determine the roles of AMPK in the protective effects of resveratrol in OAC proliferation and to elucidate the underlying mechanisms. Treatment of cultured OAC derived from human subjects or cell lines with resveratrol resulted in decreased cell proliferation. Further, inhibition of AMPK by pharmacological reagent or genetical approach abolished resveratrol-suppressed OAC proliferation, reduced the level of p27Kip1, a cyclin-dependent kinase inhibitor, and increased the levels of S-phase kinase-associated protein 2 (Skp2) of p27Kip1-E3 ubiquitin ligase and 26S proteasome activity reduced by resveratrol. Furthermore, gene silencing of p27Kip1 reversed resveratrol-suppressed OAC proliferation. In conclusion, these findings indicate that resveratrol inhibits Skp2-mediated ubiquitylation and 26S proteasome-dependent degradation of p27Kip1 via AMPK activation to suppress OAC proliferation.